Autonomous Skill Acquisition on a Mobile Manipulator - Konidaris, George; Kuindersma, Scott; Grupen, Roderic; Barto, Andrew (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
We describe a robot system that autonomously acquires skills through interaction with its environment. The robot learns to sequence the execution of a set of innate controllers to solve a task, extracts and retains components of that solution as portable skills, and then transfers those skills to reduce the time required to learn to solve a second task.